(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Today, wheat is not only of vital importance for human nutrition but is also the most widely cultivated crop globally, providing approximately 20% of daily protein and caloric intake. After rice, wheat serves as the second most important staple food crop in developing countries (Asseng S.; Guarin J., 2020). As global food demand continues to rise, there is a pressing need to increase food production, which cannot be achieved solely by expanding agricultural land (Lawlor D.W.; Mitchell R.A., 2001).